DIAGNOSTIC MONITORING FOR HISTORIC URBAN LANDSCAPE CASE STUDY: BUILDING IN VIA CARACCIOLO NAPOLI - Ciocia, Claudia; Napolitano, Teresa; Viola, Serena (European Scientific Journal, ESJ, 2013)
Anticipating the rise and degenerate of the degradation processes for urban landscape, is an area of research that requires the deployment of analysis and forecasting, informed to the impacts induced by climatic and environmental pressures on settlements. Taking into account historic areas, the study focuses upon the need to set up a practice-based research, rethinking the processes of condition’s relief, by integrating deterioration data with the prediction of the impact-induced by microclimate processes. The paper introduces as a case study, a nineteenth-century neighborhood in Naples, completed in 1869-80, with the reorganisation of the waterfront, filling the beach and constructing new buildings. The degradation reliefs, on sight and instrumental, carried out with the support of the infrared camera in three different moments of the building life cycle (2002, 2011, 2013), constitutes the knowledge base to relate degenerative phenomena with the constructive, morphological and dimensional characteristics and contextual conditions. The infrared remote sensing, long used through the two-dimensional display of the measurement of irradiation in order to evaluate the performance of the building (to detect insulation defects, thermal bridges, the heat loss through the windows, the humidity) is adopted to bind information about the phenomena taking place in location factors, climatic and environmental conditions. The observation of the related iterated and superimposed effects of decay allows the scheduling of control actions, with the intent to prevent an overrun of critical performance thresholds. A recursive approach characterizes the investigation procedure, based on forecast and verifiability.